PENGGUNNAN EKSTRAK BIJI PEPAYA (Carica Papaya L) SEBAGAI LARVASIDA NABATI TERHADAP KEMATIAN LARVA NYAMUK ANOPHELES DAN AEDES AEGYPTI INSTAR III - I. Nafi’ah; Sulistyowati Sulistyowati (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2014)
Testing has been conducted on pesticide seed water extract of papaya (Carica papaya L). This research aims to study the killing power of papaya seed extract as a botanical pesticide against mosquito larvae of Anopheles and Aedes aegypti. Larvae of Aedes aegypti and Anopheles mosquitoes respectively 350 were divided into 11 groups. Furthermore each group were sprayed with water extract of papaya seeds with 0, 20, 40, 60, 80, 100, 120, 140, 160, 180, and 200%. The results showed that the water extract of papaya seeds can kill the mosquito Anopheles larvae and A. Aegypti. Concentration of papaya seed extract is effective in killing mosquito larvae Anopheles and A. Aegypti respectively 80% and 180%. Keywords: papaya seeds, Anopheles and Aedes aegypti